LABOUR PRECARIOUS TEACHING IN SAO PAULO STATE: TWENTY YEARS OF REFORMS - Piovezan, Patricia Regina [UNESP]; Dal Ri, Neusa Maria [UNESP] (Univ Estadual Campinas, Fac Educacao, 2016)
This paper aims to investigate the implications of educational reform, in the last twenty years to the career of teaching category of Sao Paulo. We assume that the new educational policies implemented by the Education Department of the State of Sao Paulo, after approval of the Law of Directives and Bases of National Education n degrees. 9.394/96, accelerated and expanded the precarious process of the work of Sao Paulo professors in ongoing since the 1970. This study was conducted through bibliographical and documentary research, with analysis of key legislation related to the theme. The main categories used in the survey were the intensification of teachers' work, flexibility in the ways of hiring and wage squeeze. During the research we locate and analyze various laws that allow for intensification and flexible forms of employment of teachers as well as the wage squeeze caused by low wages and encouraging the expansion of policies that encourage the employment of teachers through bonus. We conclude that a series of educational reforms developed by the Sao Paulo federal and state government accelerated the casualization process of teaching the last two decades.
Keywords: Educational reforms; Labour precarious teaching; Educational policy of the State of Sao Paulo